Investigating the Correlation of Alexithymia in People with Borderline Tendencies with Impulsivity, Self-Harm and Borderline Personality Traits - Ahmad Mirgol; Rasoul Heshmati; Bahman Matinpoor (Taṣvīr-i salāmat, 2018)
Background and Objectives: The borderline personality disorder includes a cluster of syndromes and symptoms characterized by instable and impulsive behaviors. The aim of the present study was to investigate the correlation of alexithymia in people with borderline tendencies with impulsivity, self-harm and borderline personality traits. Material and Methods: In a descriptive-correlational and cross sectional research approach, 350 students from Tabriz University were selected using random cluster sampling. From this sample, 115 people with a borderline score higher than the cut-off point were chosen and labeled as people with borderline tendencies. Toronto Alexithymia Scale-20, STB, and SHI questionnaires were used to collect data. The data were analyzed using Pearson product-moment correlation and simultaneous multiple regression by SPSS software v.21. Results: The findings indicated that alexithymia has a positive and meaningful relationship with borderline personality traits (r=0.36, p Conclusion: Based on these findings, we can conclude that alexithymia and problems in identifying feelings are the main determinants of borderline personality traits and impulsivity. Also, alexithymia and problems in identifying feelings and problems in describing feelings subscales are the main determinants of self-harm.